1999
DOI: 10.1002/(sici)1521-4109(199905)11:6<412::aid-elan412>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Monitoring and Evaluation of Current and Mass Transients with the QCMB in the Millisecond Range

Abstract: An experimental set-up is described which allows the simultaneous recording of current and mass transients with millisecond resolution by using 5 MHz quartz resonators operated in a liquid environment. At the same time a mass resolution of a few nanograms is realized. It is demonstrated that this set-up allows the application of fast potential pulses to electrochemically depositastrip copper adlayers. The results proved that the obtained frequency response of the QCMB of 1 ms due to a sudden mass change has to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The advantage of the combined use of massograms and voltammograms for the study of different types of electrochemical reactions was illustrated recently by several authors. [14][15][16] It is shown that the nucleation and growth of rhodium on polycrystalline gold from concentrated chloride solutions is a typical example of the effect of slow electrode kinetics on the morphology of potentiostatic transients.…”
mentioning
confidence: 99%
“…The advantage of the combined use of massograms and voltammograms for the study of different types of electrochemical reactions was illustrated recently by several authors. [14][15][16] It is shown that the nucleation and growth of rhodium on polycrystalline gold from concentrated chloride solutions is a typical example of the effect of slow electrode kinetics on the morphology of potentiostatic transients.…”
mentioning
confidence: 99%